Strategies, Problems, and Efforts to Synergize in Integrated Social Studies Learning in Grade VIII of SMP Negeri 2 Magelang Academic Year 2014/2015 - Aulia, Amna (Universitas Negeri Semarang, 2018)
The study was conducted in the eighth grade in junior high school 1 Magelang, and data collection was done using in-depth interviews, observation, and documentation. Validation of data using triangulation techniques and triangulation of sources. Data analysis using three interactive models, namely data reduction (data reduction), data display (presentation of data), and verification (conclusion). The results showed that (1) teachers design learning strategies Integrated social science through the development of learning tools and technical preparation before the start of learning; (2) The internal problems that arise in the form of background learning teacher education is not education social studies and there are still students who are less concentrated in learning. The external problem that arises is the lack of infrastructure as well as the most burdensome in the form of a new curriculum policy that mandates delivery of achievement of the students in the form of descriptive; (3) Efforts to synergize learning that teachers are training and fellowship meeting of teachers; schools also facilitate the needs of teachers and students.